2017
DOI: 10.1021/jacs.6b11846
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin-Encapsulated Biodegradable Nanosystems for Highly Efficient Magnetic Resonance Imaging-Guided Sonodynamic Cancer Therapy

Abstract: Traditional photodynamic therapy (PDT) suffers from the critical issues of low tissue-penetrating depth of light and potential phototoxicity, which are expected to be solved by developing new dynamic therapy-based therapeutic modalities such as sonodynamic therapy (SDT). In this work, we report on the design/fabrication of a high-performance multifunctional nanoparticulate sonosensitizer for efficient in vivo magnetic resonance imaging (MRI)-guided SDT against cancer. The developed approach takes the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
411
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 583 publications
(416 citation statements)
references
References 52 publications
2
411
0
3
Order By: Relevance
“…2019, 6, 1802001 and free ICG (Figure 6e). [14,45] Quantitative analysis of the ICG fluorescence intensity distribution in the organs and tumor is shown in Figure S15 of the Supporting Information, and is in agreement with the ex vivo fluorescence imaging. These results confirmed that ICG/PFP@ HMOP-PEG could effectively extend the blood circulation time of ICG due to the PTX prodrug capping and PEGylation.…”
Section: In Vivo Pharmacokinetics and Biodistributionsupporting
confidence: 78%
See 2 more Smart Citations
“…2019, 6, 1802001 and free ICG (Figure 6e). [14,45] Quantitative analysis of the ICG fluorescence intensity distribution in the organs and tumor is shown in Figure S15 of the Supporting Information, and is in agreement with the ex vivo fluorescence imaging. These results confirmed that ICG/PFP@ HMOP-PEG could effectively extend the blood circulation time of ICG due to the PTX prodrug capping and PEGylation.…”
Section: In Vivo Pharmacokinetics and Biodistributionsupporting
confidence: 78%
“…These not only enhance the tumor cell uptake of the nanoparticles (Figure 4e-h), but also serve as an ultrasound imaging agent (Figure 4a). [14,15] HMONs and other mesoporous silica systems have been constructed for the delivery of PFP and perfluorohexane in several recent studies, [18,27] and found to act as potent bubble generators. [14,15] HMONs and other mesoporous silica systems have been constructed for the delivery of PFP and perfluorohexane in several recent studies, [18,27] and found to act as potent bubble generators.…”
Section: Wwwadvancedsciencecommentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the well-defined mesoporosity of HMSNs can enable efficient encapsulation of photosensitizers ( i.e ., protoporphyrin) for therapeutic purposes, as well as further confinement of paramagnetic Mn ions based on metalloporphyrin chelating chemistry. 188 This mesoporous structure endowed these intriguing sensitizers with remarkably enhanced MRI performance ( r 1 = 9.43 mM −1 s −1 ).…”
Section: Strategies To Achieve High Relaxivity For Mri Contrast Enmentioning
confidence: 99%
“…The optical and T 1 relaxation properties of DVDMS‐Mn‐LPs hold promises for dual‐mode contrast agent for fluorescence and MR imaging of tumours (Figure ). In fact, abundant macromolecules and nanoparticles have been used as platforms for manganese loading, resulting in improved r 1 value of chelated Mn 2+ (generally between 5 and 30 per mmol/L per seconds) . In our study, the r 1 value for DVDMS‐Mn‐LPs was about 4‐fold higher than that of the clinical approved Magnevist due to increased local concentration of Mn 2+ and lowered molecular tumbling rate in those nanocarrier systems .…”
Section: Discussionmentioning
confidence: 61%